1999
DOI: 10.1891/1061-3749.7.2.101
|View full text |Cite
|
Sign up to set email alerts
|

The Children’s Cognitive Triad Inventory: Reliability, Validity, and Congruence With Beck’s Cognitive Triad Theory of Depression

Abstract: Depression, once thought rare in children, is now more widely recognized and believed to arise from negative views of self, world, and future, according to Beck’s cognitive theory of depression. The Cognitive Triad Inventory for children measures the three negative views, and although reported as psychometrically adequate, this study extended previous analyses with confirmatory factor analysis in a sample of 122 school-aged children. Internal consistency was .82 (total scale) but ranged from .54 to .76 for sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
0
9
1
3
Order By: Relevance
“…Kaslow et al [1992] found the scale and individual subscales to be internally consistent with a sample of fourth-to seventh-grade children, r for scale ¼ .92, r for self ¼ .83, r for world ¼ .69, and r for future ¼ .85. Zauszniewski et al [1999] also observed high internal consistency for a sample of 10-to 12-year-old children, Cronbach's a ¼ .84, a for self ¼ .76, a for world ¼ .57, and a for future ¼ .69. The scale and subscales have been found to correlate significantly with measures of self-esteem and hopelessness, r ¼ .57 to .71, thereby providing support for the measure's concurrent validity [Kaslow et al, 1992].…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…Kaslow et al [1992] found the scale and individual subscales to be internally consistent with a sample of fourth-to seventh-grade children, r for scale ¼ .92, r for self ¼ .83, r for world ¼ .69, and r for future ¼ .85. Zauszniewski et al [1999] also observed high internal consistency for a sample of 10-to 12-year-old children, Cronbach's a ¼ .84, a for self ¼ .76, a for world ¼ .57, and a for future ¼ .69. The scale and subscales have been found to correlate significantly with measures of self-esteem and hopelessness, r ¼ .57 to .71, thereby providing support for the measure's concurrent validity [Kaslow et al, 1992].…”
Section: Methodsmentioning
confidence: 82%
“…Jacobs and Joseph [1997] observed similar results with 13-to 16-year-old youth. In an attempt to validate Beck's tripartite model, Zauszniewski et al [1999] factor analyzed the measure with 10-to 12-year-old children. Three factors that included cognitions about the self emerged rather than three factors about the self, the world, and the future, respectively.…”
mentioning
confidence: 99%
“…Habida cuenta de la falta de acuerdo en las diversas investigaciones sobre la dimensionalidad del test en niños (Kaslow et al, 1992;LaGrange et al, 2008;Zauszniewski et al, 1999), se sometió a prueba, mediante un Análisis Factorial Confirmatorio, la estructura trifactorial (yo, mundo y futuro) obteniendo los índices de ajuste que se exponen en la Tabla 1.…”
Section: Resultsunclassified
“…Esta discrepancia en cuanto a su dimensionalidad puede ser producto del desarrollo cognitivo propio de las edades infantiles de la muestra. Así, los resultados parecen apoyar la idea de que los pensamientos sobre el yo, mundo y futuro son tres tipos de pensamientos sobre el yo (LaGrange et al, 2008), más que tres factores discretos (Greening et al, 2005;Zauszniewski et al, 1999). En base a estos resultados, no sería necesario mantener las tres dimensiones separadas para representar la estructura latente de los pensamientos depresivos que defiende la teoría de la depresión de Beck, al menos en la infancia.…”
Section: Discussionunclassified
See 1 more Smart Citation